Psychometric Properties of the Sexual Subjetive Well-Being Scale in Young and Adults Chilean [Propiedades Psicométricas del Cuestionario de Bienestar Sexual Subjetivo en Jóvenes y Adultos Chilenos] - Vera-Villarroel, P; Contreras-Ramirez, D; Lillo-Vidal, S (Sociedad Chilena de Psicologia Clinica, 2017)
The present study evaluates the psychometric properties of subjective sexual well-being questionnaire in young and adult Chileans who residing in Santiago. The version of the scale translated into Spanish, was applied to a sample of 661 young and adults people between the ages of 18 and 54 who did not report any mental or physical illness. 49% of the sample was women and 51% of men. The psychometric properties and reliability were evaluated by exploratory factorial analysis and Cronbach’s alpha. The optimal factorial structure of the questionnaire was one factor with 4 items and had adequate reliability (α = .73), although item 4 had low factor loadings. The results indicate that the version of the subjective sexual well-being questionnaire is a valid and reliable self-administered instrument to evaluate the sexual well-being of women and men without reports of physical or mental illness. © 2017 by Sociedad Chilena de Psicología Clínica.